Experimentation of Think Pair Share learning assisted by GeoGebra software on students' mathematics learning outcomes - Rikza, Qongidahtul; Rahmawati, Arum Dwi; Mashuri, Anwas (Universitas Sarjanawiyata Tamansiswa, 2023)
This study seeks to identify learning models that influence students' mathematics learning outcomes. Based on the level of absorption, the learning outcomes of the SMK Terpadu Jannatul Firdaus students have not yet reached the KKM and the learning outcomes in mathematics are not good or low, especially in the field of quadratic function equations, due to the not optimal indicators of the learning process at the school. One solution that can be applied is the Think Pair Share (TPS) learning model assisted by GeoGebra Software. This quantitative experimental research used a quasi-experimental design, namely the Posttest Only Control Design with a population of all students of class XI at SMK Terpadu Jannatul Firdaus. The sampling technique used cluster random sampling with three randomly selected samples, two as the experimental class and one as the control class. The first experimental class was taught through the application of the TPS learning model assisted by GeoGebra Software, the second experiment used the TPS learning model only, and the third was used as a control class using the conventional model. The research instrument uses a mathematics learning achievement test instrument. The research hypothesis uses Anova test and post-Anova test. The results showed that students who were taught using the TPS model assisted by the GeoGebra Software obtained a better average and outperformed compared to students who were taught using the conventional model or only the TPS model, as calculated in this study, Fcount was 8.620, which was greater than Ftable, which was 3.096.